The O. Henry Awards Prize Stories, 2003 - Furman, Laura (New York : Doubleday, 2003)
A new edition of the annual collection of short stories judged to be the best in America and Canada for 2003.
Introduction / Laura Furman -- The thing in the forest / A.S. Byatt -- The shell collector / Anthony Doerr -- Burn your maps / Robyn Joy Leff -- Lush / Bradford Morrow -- God's goodness / Marjorie Kemper -- Bleed blue in Indonesia / Adam Desnoyers -- The story / Edith Pearlman -- Swept away / T. Coraghessan Boyle -- Meanwhile / Ann Harleman -- Three days. A month. More. / Douglas Light -- The high road / Joan Silber -- Election eve / Evan S. Connell -- Irish girl / Tim Johnston -- What went wrong / Tim O'Brien -- The American embassy / Chimamanda Nqozi Adichie -- Kissing / William Kittredge -- Sacred statues / William Trevor -- Two words / Molly Giles -- Fathers / Alice Munro -- Train dreams / Denis Johnson.
"An Anchor original"--Title page verso.
O. Henry Memorial Award, 2003.
Keywords: Short stories, American; United States -- Social life and customs -- Fiction